Comparative study of aspiration and non-aspiration cytology of palpable breast lumps and correlation with histopathology - Koirala, S (Journal of Pathology of Nepal, 2014)
Background: Breast lump is one of the most common presentations in surgical outpatient departments with anxiety regarding a possible malignancy. Hence a quick diagnosis of a lump in the breast is essential. Fine needle aspiration cytology is an ideal initial diagnostic modality in breast lumps. There is an alternative method of performing needle aspiration, known as fine needle capillary cytology where the specimen is obtained using just a needle without aspiration. Materials and Methods: This hospital-based cross sectional analytical study was carried out in Department of Pathology in National Academy of Medical Sciences, Bir Hospital for one year. The objective of this study was to compare aspiration and non-aspiration cytology of palpable breast lumps and correlation with histopathology. Results: The five criteria scored for each technique were background blood, amount of cellular material, cellular degeneration, cellular trauma and architectural preservation. Compared to fine needle aspiration cytology, fine needle capillary cytology yields less bloody smears with minimal degenerative changes and offers more diagnostically superior specimens. Fine needle aspiration cytology, on the other hand, gives a good yield of diagnostic material. Conclusion: Fine needle aspiration cytology and fine needle capillary cytology are quick, easy, safe and cost-effective techniques. . A high sensitivity and specificity of cytological diagnosis in this study proves that it is comparable to final histology report in its diagnostic efficiency. Thus, fine needle aspiration cytology is a very important preliminary diagnostic test in palpable breast lumps and the results show a high degree of correlation with the final histopathology report. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11501 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 639-643